Development of a geo-informatics database of abattoirs in Ibadan, Nigeria for epizootiological surveillance (2005)
Animal diseases and health problems transcend local and international kudus. requiring attention to geographical, spatial and temporal considerations before effective prevention and control could be implemented. The application of geo-information technologies has been on for decades to facilitate diseases reporting, monitoring, surveillance, prediction and intervention (prevention/treatment/control) programmes. Low stock of livestock base data is one of the challenges/limitation to the adoption/application of modern geographic information technologies in the control of epizootics m Africa, including Nigeria. Abattoris are typical foci for epizootiological studies of animal diseases, including zoonotic disease of public health importance. This paper highlights the use of Geographical Inhumation Systems and Global Positioning System technologies lot the establishment of a spatial baseline geographical data of some abattoirs in Ibadan, one of Africa’s largest cities. Such a baseline data could form a basis for the running of an effective veterinary inhumation system for disease diagnosis, monitoring and surveillance